The Effect of Anxiety on Sleep Quality among COVID-19 Survivors in Barangay North Bay Boulevard South of Navotas City (Global Journal of Medical Research, 2023)
Background The outbreak of COVID-19 has impacted the mental health of the people The study purpose is to look into the different factors or levels of anxiety that influence the sleep quality of a COVID-19 survivor in Barangay North Bay Boulevard South of Navotas City Objectives This study aimed to investigate the effect of anxiety on sleep quality of COVID-19 survivors in Barangay North Bay Boulevard South of Navotas City Materials and Methods In this cross-sectional study data were collected between May 7 2022 to May 25 2022 The total population is 1891 with a sample size of 336 Informed consent form GAD7 and Pittsburgh sleep quality index questionnaire were used as data collection tools
Keywords: anxiety; sleep quality; COVID-19